Traumatic experiences, aggression and internet addiction in university students - İnan Budak, Merve; Akarsu, Özlem; Okanlı, Ayşe; Adıgüzel, Vesile (Journal of Dependence, 2022)
Objective: The aim of this study is to examine the level of traumatic experiences, aggression and internet addiction among university students and the relationship between them.Method: This study is a descriptive and correlational research. The research was conducted with 294 students studying at the health sciences faculty of a state university. Research data were collected through Childhood Traumas Scale (CTS), Buss-Perry Aggression Scale and Young Internet Addiction Test Short Form.Results: According to the results of the analysis, the trauma levels of the majority of the students (51%) were low. When the subscale scores are examined, it is seen that the highest mean score is emotional neglect, and the lowest mean score is sexual abuse. A positive and significant relationship was found between childhood traumas and verbal aggression sub-dimension. In addition, a positive and significant relationship was found between childhood traumas and internet addiction.Conclusion: Childhood abuse experiences may have a long-term effect on various aspects of behavior and psychiatric comorbidities.
Keywords: Childhood Traumas; Aggression; Internet Addiction